Education and science: current trends - Bakhmisova M. A., Sakmarova L. A., Prisyazhnaya I. M., Prisiazhnaia S. P. (Education and science: current trends, 2018)
this monograph deals with the problem of threshing and grain separation in two-phase threshing device of the combine. During combine harvesting, high-quality seeds of soya fall into the total mass of the grain, pass through the entire threshing stage by the first and second drums, cleaning, crushing into halves and small parts and sorted out after post-harvest processing. The authors conclude that with this soybean harvesting technology, more than 50% of the seeds are not receiving the natural resource of yield gain, since the different-quality seeds are not separated or collected separately during the operation of the air-screen cleaning of the combine. According to earlier studies, soybean yield losses are 2.7–3.3 dt/ha.
Keywords: сбор; collection; соя; harvesting; сепарация; soybean; повреждение; уборка; двухфазный обмолот; качественные семена; two-phase threshing; damage; separation; quality seeds